2018
DOI: 10.1016/j.sjbs.2017.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization of silver phyto nanoparticles and their impact on growth potential of Lupinus termis L. seedlings

Abstract: The current study reports rapid and easy method for synthesis of eco-friendly silver nanoparticles (AgNPs) using leaves extract as a reducing and covering agent. The bio-reductive synthesis of AgNPs was monitored using a scanning double beam UV-vis spectrophotometer. Transmission electron microscopy (TEM) was used to characterize the morphology of AgNPs obtained from plant extracts. X-ray diffraction (XRD) patterns of AgNPs indicate that the structure of AgNPs is the face centered cubic structure of metallic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(31 citation statements)
references
References 26 publications
3
28
0
Order By: Relevance
“…Seedlings of Lupinus termis treated with high concentrations of AgNPs (300-500 ppm) responded with a reduction in shoot and root elongation and decreased biomass accumulation. However, AgNPs at 100 ppm stimulated shoot and root growth [37]. Similarly, positive effects of low-concentrated solution of AgNP on seedling development were reported in Pisum sativum [38].…”
Section: Discussionmentioning
confidence: 66%
“…Seedlings of Lupinus termis treated with high concentrations of AgNPs (300-500 ppm) responded with a reduction in shoot and root elongation and decreased biomass accumulation. However, AgNPs at 100 ppm stimulated shoot and root growth [37]. Similarly, positive effects of low-concentrated solution of AgNP on seedling development were reported in Pisum sativum [38].…”
Section: Discussionmentioning
confidence: 66%
“…Previous studies indicated that Ag-NPs induced the variable mode of action on crop plants [23]. In this study, exposure to plant-mediated Ag-NPs resulted in a significant reduction in plant elongation, fresh weight of shoot and root, and total chlorophyll content of seedling of Lupinus termis L. Moreover, 0.5 mg/l of Ag-NPs decreased carbohydrates and protein contents and increased accumulation of proline in seedlings [24]. On the contrary, 50 and 75 mg/l of biologically synthesized Ag-NPs protected wheat plants against heat stress and improved plant growth and biomass as compared to control [25].…”
Section: Introductionmentioning
confidence: 56%
“…1 filter paper. In order to produce nanosilver, a typical synthesis procedure is carried out (Al-Huqail et al 2018;Raj et al 2018), using the (1 mM AgNO 3 ) solution. The synthesis of AgNPs was carried out as follows: The extract was combined with AgNO 3 , in equal amounts.…”
Section: Preparation Of Silver Nanoparticlesmentioning
confidence: 99%
“…Ma et al (2010) examined the toxic effects of different sizes of AgNPs (20-80 nm) on Arabidopsis thaliana seedlings, and they observed an increase in toxicity after increasing the concentration of AgNPs. Al-Huqail et al (2018) examined the morphological and anatomical changes in Lupinus termis leaves in response to different concentrations of green AgNPs. The authors of this work assessed the phytotoxic activity of silver nanoparticles biosynthesized with the use of Veronica officinalis extract against Lepidium sativum and Linum flavum seeds.…”
Section: Introductionmentioning
confidence: 99%